Safe-sex knowledge, self-assessed HIV risk, and sexual behaviour of young Portuguese women - Costa, Eleonora C.V. (2018)
ABSTRACT - Background: Young women make up most cases of HIV infection in Portugal (e.g., 26% in 2012), but their sexual behaviour, ability to recognize sexually transmitted disease (STD) risk in partners, and knowledge and practice of safe sex are underresearched. Methods: We studied these issues in a group of 177 women from Northern Portugal, together with their social, educational, and religious background. The women filled out several self-report questionnaires developed in the USA that have been adapted and validated for use in Portugal. They assess HIV knowledge, risk perception, and sexual risk behaviour. Results: We documented good knowledge about HIV transmission and prevention, although there are still some myths; 79.9% of the women knew that condoms prevent HIV transmission, but only 46% of them declared to use them regularly. Thus, knowledge does not imply adequate preventive behaviour. Women lacking higher education had poorer knowledge of HIV biology and of partner HIV risk. Despite being aware of HIV cases in their communities, most women deemed themselves at little risk, especially those lacking higher education, with many arguing that monogamy protects them, and, importantly, many preferring to ignore their partners’ current and past behaviour when assessing their exposure. Conclusion: These results point to important intervention targets for campaigns to curb STD infections among young women.